A Study of Tapping by the Unaffected Finger of Patients Presenting with Central and Peripheral Nerve Damage - Zhang, Lingli; Han, Xiuying; Li, Peihong; Liu, Yang; Zhu, Yulian; Zou, Jun; Yu, Zhusheng (Frontiers in Human Neuroscience, 2015)
Aim: Whether the unaffected function of the hand of patients presenting with nerve injury is affected remains inconclusive. We aimed to evaluate whether there are differences in finger tapping following central or peripheral nerve injury compared with the unaffected hand and the ipsilateral hand of a healthy subject. Methods: 30 right brain stroke patients with hemiplegia, 30 left arm peripheral nerve injury cases and 60 healthy people were selected. We tested finger tapping of the right hands, and each subject performed the test twice. Results: Finger tapping following peripheral nerve injury as compared with the unaffected hand and the dominant hand of a healthy person was significantly higher than was found for central nerve injury (P<0.05). Finger tapping of the male peripheral group’s unaffected hand and the control group’s dominant hand was significantly higher than the central group (P<0.001). However, finger tapping of the female control group’s dominant hand was markedly higher than the central group’s unaffected hand (P<0.01, P=0.002), the peripheral group’s unaffected hand (P<0.05, P=0.034). Conclusion: The unaffected function of the hand of patients with central and peripheral nerve injury was different as compared with the ipsilateral hand of healthy individuals. The rehabilitation therapist should intensify the practice of normal upper limb fine activities and coordination of the patient.